Model Komunikasi Organisasi Dalam Prespektif Kelurahan di Bali dalam Menghadapi Pandemi Covid-19 - Mariana, I Ketut Adi; Sofyan, Nur; Heryana, Alifya Ikhsanty (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
Covid-19 pandemic has been affecting many sectors, especially for the tourism sector itself. As we know, most of the people of Bali Province depend on the tourism sector for their living. In the presence of this pandemic, caused a lot of people to experience the obstacles, such as work from home, unpaid leave, even the termination of employment. In this case, the government of Denpasar city which is the capital city of Bali put a lot of effort to overcome the spread of Covid-19 that happened in that region. Because of that, the researchers take this case at Renon village, Denpasar city from doing research and look at the potential conflict towards organization communication that happened between the people and the authorized party in handling the spread of the virus in that region. Therefore, this research uses field research with a qualitative descriptive case study research method. This research data that used for this research sourced from a field study, which is the result of the interview and the observation with the interviewees, also from the literature that already been published, related, and support this research. The result of this research can be concluded into, that the action from handling the conflict by the authorized party with the people of Renon village who has conflict is by the Integrating and Compromising methods. Therefore, the researchers hopefully can give thought contribution to managing conflict of the organization communication that happened in handling the case of the Covid-19 pandemic.